Healthcare Capacity, Health Expenditure, and Civil Society as Predictors of COVID-19 Case Fatalities: A Global Analysis - Khan, Jahidur Rahman; Awan, Nabil; Islam, Md. Mazharul; Muurlink, Olav (Frontiers in Public Health, 2020)
Background The rapid growth in cases of COVID-19 has challenged national healthcare capacity, testing systems at an advanced ICU, and public health infrastructure level. This global study evaluates the association between multi-factorial healthcare capacity and case fatality of COVID-19 patients by adjusting for demographic, health expenditure, population density and prior burden of noncommunicable disease. It also explores the impact of government relationships with civil society as a predictor of infection and mortality rates. Methods Data were extracted from the Johns Hopkins University database, World Bank records and the National Civic Space Ratings 2020 database. This study used data from 86 countries which had at least 1000 confirmed cases on 30th April 2020. Negative binomial regression model was used to assess the association between case fatality (a ratio of total number of confirmed deaths to total number of confirmed cases) and healthcare capacity index adjusting for other covariates. Findings Regression analysis shows that greater healthcare capacity was related to lesser case-fatality (incidence rate ratio [IRR] 0·5811; 95% confidence interval [CI] 0·4727 to 0·7184; p<0·001) with every additional unit increase in the healthcare capacity index associated with a 42% decrease in the case fatality. Health expenditure and civil society variables did not reach statistical significance but were positively associated with case fatalities. Interpretation Based on preliminary data, this research suggests that building effective multidimensional healthcare capacity is the most promising means to mitigate future case fatalities. The data also suggests that government’s ability to implement public health measures to a degree determines mortality outcomes.